Ризики розвитку людського капіталу в умовах війни в системі координат соцієтальної системи* - В. В. Близнюк; Л. Д. Яценко (Bulletin of the Academy of Labor, Social Relations and Tourism. Series: Economics, Psychology and Management, 2025)
*Editorial Note This note concerns the article: Blyzniuk, V. V., & Yatsenko, L. D. (2025). Risks of Human Capital Development in the Context of War in the Coordinate System of the Societal System. Visnyk Akademii Pratsi, Sotsialnykh Vidnosyn i Turyzmu. Series: Economics, Psychology and Management, No. 3. https://doi.org/10.54929/3041-2390-2025-03-01-02 Following a formal submission from Dr. Olena Sushyi, Doctor of Public Administration, regarding the possible improper use of elements from her earlier academic work: Sushyi, O. V. (2019). Nation-Building Process in the Coordinates of the Societal Crisis in Ukraine. Scientific Studies in Social and Political Psychology, 43, 7–19. http://nbuv.gov.ua/UJRN/Nsspp_2019_43_3 the editorial board initiated an internal review in accordance with COPE (Committee on Publication Ethics) recommendations. Outcome of the review: The authors submitted a revised version of the article in which: The original authorial content was clearly delineated from referenced ideas; Proper citation of Sushyi (2019) was included; The specific elements of the original study that were expanded and adapted to the context of human capital research during wartime were explicitly identified. Editorial conclusion: The editorial board confirms that the revised version of the article meets the standards of academic integrity. The publication remains available in its updated and corrected form. This editorial note is issued to ensure transparency in the editorial process and to inform readers about the nature of the revisions. Date of editorial note publication: May 9, 2025 Editorial Board Bulletin of the Academy of Labor, Social Relations and Tourism. Series: Economics, Psychology and Management ________________________________________________________________ Human capital is a driver of socio-economic development, which significantly actualizes the need to study the conditions of its formation. The study is devoted to the systematization of risks and consequences of deterioration of the quality of the societal system as a whole and its separate component - human capital, whose evolutionary development forms new qualitative characteristics of the societal system. Violation of the balance of functioning of institutional subjects of the social order leads to anomalies. Given that the societal structure of society is never a simple return to the previous “norm”, the authors substantiate the expediency of considering the architectonics of human capital quality in post-war development in the coordinates characterizing the relevant sections of the societal system, namely: systemic, existential and socio-psychological. This approach allowed us to identify the peculiarities of ensuring the quality of human capital in each of the coordinate systems. The analysis of the current situation in Ukraine shows that the risks generated in the labor, demographic, educational spheres and the risks associated with the availability and quality of medical services are of particular concern. It is noted that the peculiarities of the manifestation of modern risks are the deterioration of the demographic situation, the reduction of the possibilities of reproduction of human capital, the violation of balances in the labor market, the decline in the welfare of the population, the deterioration of the financial condition of social benefit funds and the high level of burden on them. Risks give rise to the possibility of negative changes, create the danger of dysfunction of social institutions, inhibition of social reproduction, production processes, transmission of social norms and values; formation of social instability and tension. Identification of a number of problems of accumulation and use of human assets in the context of a prolonged war allowed the authors to systematize the risks and consequences of ensuring favorable conditions for the formation of human capital in the face of its significant losses. This made it possible to outline the priority vectors of state policy in the field of human capital reproduction.